Physiological Responses and Performance during an Integrated High-Intensity Interval Aerobic and Power Training Protocol - Ilias Iason Psarras; Gregory C. Bogdanis (MDPI AG, 2024)
This study compared the acute physiological responses and performance changes during an integrated high-intensity interval aerobic and power protocol. Sixteen moderately trained athletes (age: 20.1 ± 2.2 years, body height: 180.0 ± 6.5 cm, body mass: 75.7 ± 6.4 kg, VO2max: 55.8 ± 4.3 mL/kg/min) performed a 2 × 6 min interval training protocol with 2 min passive recovery between sets on two different occasions in random and counterbalanced order. Each 6 min set included repeated periods of 15 s exercise interspersed with 15 s passive rest. On one occasion (RUN), all exercise periods included running at 100% of maximal aerobic speed, while on the other occasion an integrated protocol was used (INT) in which each of the two 6 min sets included 4 × 1.5 min periods of running exercise at 100% of maximal aerobic speed in combination with jumping (i.e., 2 × 15 running with 15 s rest and 1 × 15 s drop jumping with 15 s rest). Time spent above 85% HRmax was two-fold higher in INT compared to RUN (8.5 ± 3.6 vs. 4.3 ± 3.9 min, respectively, p = 0.0014). Interestingly, heart rate increased above 95% HRmax only in INT and almost no time was spent above 95% HRmax in RUN (1.4 ± 1.9 vs. 0.1 ± 0.2 min, respectively, p = 0.008). Blood lactate concentration at the end of the second set of INT was higher than RUN (7.3 ± 3.2 vs. 4.6 ± 2.7 mmol/L, p = 0.002). Countermovement jump was higher in INT after the end of second set by 6.4% (p = 0.04), 6.7% (p = 0.04), 7.8% (p < 0.01) and 7.3% (p < 0.001), at 2, 6 and 8 min after set 2. In conclusion, the comparison between INT and RUN shows that INT not only elicits higher physiological and metabolic responses, but also acutely enhances neuromuscular performance for at least 8 min after the end of exercise. The integrated running/jumping high-intensity interval exercise approach could be a very useful and time efficient method for strength and conditioning coaches, especially in team sports, in which the time available for the improvement of physical parameters is limited.